Ethical and Legal Considerations on Organ Procurement from Executed Prisoners in China - Wu, Yijin (Acta Bioethica, 2020)
In the past several decades, due to the severe shortage of transplantable organs, organ procurement from executed prisoners have been used to transplant organs, which goes against international ethics standards. As of January 2015, China phased out the use of executed prisoner organs and embarked on its transplant reform. Since then, many efforts have been made to meet the international ethics guidelines on organ transplants. In this study, we aim to elaborate on the status quo of organ procurement from executed prisoners from the perspective of ethics and law. Although China has made great progress in organ donation and transplantation, some Western transplant surgeons and bioethicists still hold outdated views on organ donation and transplantation in China, which will not bring any benefits to its development and will alienate it from the international transplant community. In this study, we propose that both the international transplant society and Chinese transplant community, with mutual cooperation and trust, should jointly make efforts to advance the development of organ donation and transplantation in China.